2022
DOI: 10.1080/20018525.2022.2101599
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, physical capacity and sedentary behavior among asthma patients

Abstract: BACKGROUND : Although exercise and daily physical activity (PA) have long been known to benefit patients with chronic disorders, knowledge is limited regarding asthma. OBJECTIVE : In a Danish setting, our aim was to measure physical activity, sedentary behavior, and physical capacity among patients with asthma. We hypothesized that people with severe asthma would be less active and more sedentary than their mild-moderate counterparts. METHODS : Adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A total of 17 studies explored correlates (k = 13) [ 19 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 51 , 52 , 53 ] or determinants (k = 6) [ 22 , 41 , 43 , 46 , 47 , 48 , 50 ] of physical activity or sedentary behaviour; most (82%) were of cross-sectional design ( Table 2 ). Of the 17 studies, 10 (59%) assessed physical activity or sedentary behaviour with pedometers or accelerometer devices ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 17 studies explored correlates (k = 13) [ 19 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 51 , 52 , 53 ] or determinants (k = 6) [ 22 , 41 , 43 , 46 , 47 , 48 , 50 ] of physical activity or sedentary behaviour; most (82%) were of cross-sectional design ( Table 2 ). Of the 17 studies, 10 (59%) assessed physical activity or sedentary behaviour with pedometers or accelerometer devices ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 51 , 53 ] reported correlations between health-related variables and sedentary behaviour, and no study sought to identify sedentary behaviour determinants. Both of the abovementioned studies reported correlations between sedentary behaviour and asthma control, pulmonary function, eosinophilic inflammation, airway inflammation or QoL [ 51 , 53 ]. Ricketts et al [ 53 ] reported correlations between sedentary behaviour and exercise capacity, dyspnoea, body mass, psychological health, and medication usage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association was observed between VO 2peak and pulmonary function. In adults with mild-to-moderate and severe asthma, Hansen et al [17] observed comparable fitness (39.3 ± 1.5 ml kg − 1 min − 1 and 36.7 ± 1.3 ml kg − 1 min − 1 , respectively). However, significant associations were observed between VO 2 max , body mass index (BMI), airway inflammation and asthma control.…”
Section: Functional and Exercise Capacity In People With Asthmamentioning
confidence: 94%
“…Since 2020, six observational studies have evaluated functional and/ or exercise capacity in people with asthma [12][13][14][15][16][17] (Table 1). Gianfrancesco et al [12] assessed functional capacity via the 6-min walk test and Glittre ADL-test (TGlittre) in a large cohort of children and adolescents (aged 7-17 years).…”
Section: Functional and Exercise Capacity In People With Asthmamentioning
confidence: 99%